A função f é definida por f(x) =ax+b . Sabe-se q f(-1)=7 e f(1)=3.O valor de f(3) é:
Soluções para a tarefa
Respondido por
1
f(-1)= -a + b = 3
f(1) = a + b = 1 (+
----------------------------
2b = 4
b = 2
f(1) = a + 2 = 1 -> a = -1
Por tanto,
f(3) = -1x3 + 2 = -1
f(3) = -1
f(1) = a + b = 1 (+
----------------------------
2b = 4
b = 2
f(1) = a + 2 = 1 -> a = -1
Por tanto,
f(3) = -1x3 + 2 = -1
f(3) = -1
Respondido por
1
Boa tarde Cauu
3 y 1 3 y
-1 7 1 -1 7
1 3 1 1 3
det = 21 + y - 3 - 7 - 9 + y = 0
2y + 2 = 0
2y = -2
y = -1
f(3) = -1
3 y 1 3 y
-1 7 1 -1 7
1 3 1 1 3
det = 21 + y - 3 - 7 - 9 + y = 0
2y + 2 = 0
2y = -2
y = -1
f(3) = -1
Perguntas interessantes
Saúde,
11 meses atrás
Matemática,
11 meses atrás
Matemática,
11 meses atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás